Peripheral Territories and Intersectionalities: Experiences of oppression and resistance in physical and digital-informational spaces (Intercom - Brazilian Journal of Communication Sciences, 2026)
Digital-informational territories have been constituted as a form of expression and expansion of physical territories, especially in relation to the oppressions experienced by Black, People of Color, poor, and women inhabitants of urban peripheries. Based on an analysis that considers locality as a category of difference, along with race, class, and gender, we mapped and observed four social initiatives that operate at the interface between the physical/urban/peripheral and the digital-informational. These initiatives seek, through the appropriation and re-signification of these technologies, to subvert the logic of domination, exclusion, and discrimination that prevails both in the spatial design of cities and in the development of modern communication technologies.
Keywords: Peripheral territories; Digital-informational territories; Intersectionality; Digital networks; Social initiatives